Helminth parasites - masters of regulation - Maizels, Rick M.; Balic, Adam; Gomez-Escobar, Natalia; Nair, Meera; Taylor, Matt D.; Allen, Judith E. (Immunological reviews, 2004)
Immune regulation by parasites is a global concept that includes suppression, diversion, and conversion of the host immune response to the benefit of the pathogen. While many microparasites escape immune attack by antigenic variation or sequestration in specialized niches, helminths appear to thrive in exposed extracellular locations, such as the lymphatics, bloodstream, or gastrointestinal tract. We review here the multiple layers of immunoregulation that have now been discovered in helminth infection and discuss both the cellular and the molecular interactions involved. Key events among the host cell population are dominance of the T‐helper 2 cell (Th2) phenotype and the selective loss of effector activity, against a background of regulatory T cells, alternatively activated macrophages, and Th2‐inducing dendritic cells. Increasingly, there is evidence of important effects on other innate cell types, particularly mast cells and eosinophils. The sum effect of these changes to host reactivity is to create an anti‐inflammatory environment, which is most favorable to parasite survival. We hypothesize therefore that parasites have evolved specific molecular strategies to induce this conducive landscape, and we review the foremost candidate immunomodulators released by helminths, including cytokine homologs, protease inhibitors, and an intriguing set of novel products implicated in immune suppression.